Biometric relationships of ocular components in esotropic amblyopia - Debert,Iara (2012)
PURPOSE: To investigate the contribution of the individual ocular components, i.e. anterior chamber depth, lens thickness and vitreous chamber depth, to total axial length in patients with esotropic amblyopia. METHODS: The study population consisted of 74 children, aged between 5 and 8 years: thirty-seven patients with esotropic amblyopia and 37 healthy volunteers (control group). The participants underwent a comprehensive ophthalmological examination, including cycloplegic refraction and A-scan ultrasonography. Anterior chamber depth, lens thickness, vitreous chamber depth and total axial length were recorded. Paired Student's t-tests were used to compare biometric measurements between amblyopic eyes and their fellow eyes and between right and left eyes in the control group. To evaluate the contribution of the ocular components to the total axial length, we report the individual components as a percentage of total axial length. RESULTS: The comparison between amblyopic and fellow eyes regarding the individual contribution from ocular components to the total axial length revealed greater contribution from lens thickness (P=0.001) and smaller contribution from vitreous chamber depth (P=0.001) in amblyopic eyes, despite similar contribution from anterior chamber depth (P=0.434). The comparison between right and left eyes in the control group showed similar contributions from anterior chamber depth (P=0.620), lens thickness (P=0.721), and vitreous chamber depth (P=0.483). CONCLUSIONS: This study shows differences between amblyopic and non-amblyopic eyes when the total axial length is broken down into the individual contribution from the ocular components.